Investigating impact of five build parameters on the maximum flexural force in FDM specimens – a definitive screening design approach. Issue 6 (17th October 2017) - Luzanin, Ognjan; Guduric, Vera; Ristic, Ivan; Muhic, Simon
Abstract : Purpose: The purpose of this study was to examine the impact of five key build parameters – layer thickness, deposition angle, infill, extrusion speed and extrusion temperature, and their interactions – on the maximum flexural force in specimens which are made of polylactic acid (PLA). Design/methodology/approach: Through a previous study on the flexural properties of PLA specimens, a statistically significant effect of layer thickness was indicated, requiring further experimentation to establish the values of quadratic term in the model, as well as to perform optimization. Instead of performing a conventional Central Composite Design, a novel, definitive screening design (DSD) was used as statistical method. DSD allowed the reduction of the number of runs required for optimization while minimizing aliasing. Findings: Significance of deposition angle and infill as main effects was established. Moreover, significant two-way interactions between infill/layer thickness and infill/extrusion speed were detected and discussed. The optimization procedure showed that minimum level of deposition angle, maximum levels of extrusion speed and infill and near mid-level of layer thickness yield maximum flexural force. Research limitations/implications: In this study, the three levels of infill were 0.1, 0.2 and 0.3, which corresponds to 10, 20 and 30 per cent of infill, respectively. In everyday practice, infill is usually kept within this range since it allows time-efficiency, i.e. significant reduction of build time. Though, unsurprisingly, higher infill is positively correlated with flexural strength, this study provides practical directions for optimal selection of other key parameters when working with low infill values. Social implications: Optimal 3D printing with low infill can contribute to lower material waste and pollution, while PLA plastic's biodegradability remains high on the environment protection agenda. Originality/value: According to available literature, no previous studies have investigated the FDM extrusion of PLA material using a combination of low infill, deposition angle, layer thickness, extrusion speed and extrusion temperature.